A disputa pelo poder no Rio Grande do Sul : a participação estrangeira no conflito de 1923 - Leão, Lúcio Antônio Rodrigues (2009)
This work on the fighting in Rio Grande do Sul during the Old Republic focuses on whether the different forms of use of power by the state government, emphasizing the participation and recruitment of "mercenaries" in the Revolution of 1923, as well as an analysis of struggles. Republicans and Federalists were divided in confronting the power before the Revolution of 1923, which would cause the election of 1922, when Assis Brazil (federal) had been defeated at the polls by Borges (Republican). The political differences caught in Rio Grande do Sul between Federalists and Republicans, often went beyond borders, demonstrating the power to reach these regional elites struggle for power in the state